Manganese-catalyzed alpha-olefination of nitriles with secondary alcohols - Yadav, Vinita; Landge, Vinod G.; Subaramanian, Murugan; Balaraman, Ekambaram (ACS Catalysis, 2020)
An expedient catalytic approach for alpha-olefination of nitriles using secondary alcohols with the liberation of molecular hydrogen and water as the only byproducts is reported. This reaction is catalyzed by a molecularly defined manganese(I) pincer complex and operates in the absence of any hydrogen acceptors. A broad range of substrates including cyclic, acyclic, and benzylic alcohols, as well as various nitrile derivatives, such as arylmethyl and heteroarylmethyl nitriles, are employed in the reaction to provide a diverse range of alpha-vinyl nitriles in good to excellent yields. Mechanistic studies showed that the reaction proceeds via dehydrogenative pathway and the activation of alpha(C-H) bond of the alcohol is the rate-determining step.
Keywords: acceptorless dehydrogenation; Alcohol; alpha-olefination; Hydrogen; manganese